Encephalopathy Associated with Autoimmune Thyroid Disease: A Potentially Reversible Condition - Inês Correia; Inês B. Marques; Rogério Ferreira; Lívia Sousa (Case Reports in Medicine)
Autoimmune thyroid disease may occasionally associate with unspecific neurological symptoms, which are more commonly insidious, include cognitive or behavioural symptoms, and may associate with tremor, myoclonus, or ataxia. We report a 61-year-old female patient who presented with chronic headache, insidious mood, and cognitive disturbance which evolved in a few months to dementia associated with exuberant limb myoclonus. Diagnostic workup revealed high anti-thyroid peroxidase antibody titers and an inflammatory CSF profile, and it was negative for other possible etiologies. Treatment with steroids induced significant improvement. The diagnosis of encephalopathy associated with autoimmune thyroid disease is still controversial given the fact that the clinical presentation and diagnostic workup are unspecific, the pathophysiology is still undetermined, and the diagnosis is mostly of exclusion. No direct correlation is found between anti-thyroid antibody titers and clinical presentation, and it is currently speculated that other still unrecognized antibodies may be responsible for this clinical entity. It is extremely important to recognize this entity because it is potentially treatable with immunotherapies. It is also increasingly recognized that clinical improvement with first-line treatment with steroids may be absent or incomplete, and other immunotherapies as immunosuppressants, intravenous immunoglobulin, or plasma exchange must be attempted in the clinical suspicion of EEAT.